1997
DOI: 10.1353/hpu.2010.0034
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Return Visits to a Homeless Clinic

Abstract: Associations between characteristics of homeless clients and their return visits to a nurse-managed primary health care clinic were examined using a retrospective chart review of 1,467 records from clients seen between 1991 and 1994. Client characteristics examined included age, education, race, gender, sheltered status, report of chronic disease, and report of family living in the area. Only 47 percent of clients made return visits to the clinic. Logistic regression indicated that those with reported chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Each of these conditions is more prevalent in black children. 39 McConnochie et al 40 found differences in hospitalizations of young infants relating to socioeconomic status within Rochester. Parental reporting of child health and nutrition is poorer in the Hispanic population than in the general public.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these conditions is more prevalent in black children. 39 McConnochie et al 40 found differences in hospitalizations of young infants relating to socioeconomic status within Rochester. Parental reporting of child health and nutrition is poorer in the Hispanic population than in the general public.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Unsheltered people frequently have serious mental illness, [3][4][5] cognitive disorders, 6 substance use disorders, [5][6][7][8] co-occurring mental health and substance use conditions, 7 and chronic health conditions. 5,9 Although their needs are high, they tend to receive acute rather than preventive care 10 and less frequent outpatient encounters. 3,7 Studies show that people living in unsheltered situations are at increased risk for premature death 11 and that those who died while in unsheltered situations had high rates of chronic medical illness, serious mental illness, substance use disorders, and acute care utilization.…”
mentioning
confidence: 99%
“…If the longerterm community residents who are homeless and who express the fear of loneliness significantly more than shelter residents will not use the shelter nursing clinic, they may not be reached by the existing health care system. In addition to providing nursing care, nurse-managed clinics can provide the case management that is so often needed to pull in appropriate community resources and ensure continuity of care (Capan, Beard, & Mashburn, 1993;Wagner & Menke, 1992;Macnee & Forrest, 1997). Such clinics can benefit their communities in many ways.…”
Section: Discussionmentioning
confidence: 99%